Relationship between Gadget Use and Learning Concentration Kedai Damar Village, Tebing Tinggi Subdistrict, Serdang Bedagai Regency - Haryani, Mutiara Hafidzah Tri; Anggesti, Indi; Situmeang, Monica; Apriliya, Deswita; A’yuni, Nur; Eliska, Eliska (Indonesia Berdaya, 2023)
Changing times emerge along with advances in technology created by humans, the more sophisticated technology is, the greater its influence on individuals throughout the world and the more individuals who want to have and want to be able to master sophisticated technology. Learning concentration is the main asset for students in receiving material and is an indicator of successful implementation of learning. Theoretically, if student concentration is low, it will result in low quality activities and can lead to a lack of seriousness in learning. The method used to obtain the research results contained in this article is qualitative with a case study approach. Peliti has carried out direct observations in Kedai Damar Village, Tebing Tinggi District, Serdang Bedagai Regency, this process took place from 18 July to 18 August 2023. The results show that more than half have knowledge about gadgets, but do not know how to use gadgets properly. correct, thus disturbing the student's concentration.